2013
DOI: 10.1186/alzrt206
|View full text |Cite
|
Sign up to set email alerts
|

Would you want to know? Public attitudes on early diagnostic testing for Alzheimer's disease

Abstract: IntroductionResearch is underway to develop an early medical test for Alzheimer's disease (AD).MethodsTo evaluate potential demand for such a test, we conducted a cross-sectional telephone survey of 2,678 randomly selected adults across the United States and four European countries.ResultsMost surveyed adults (67%) reported that they are "somewhat" or "very likely" to get an early medical test if one becomes available in the future. Interest was higher among those worried about developing AD, those with an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 49 publications
6
54
0
Order By: Relevance
“…However, in support of disclosure, a general questionnaire study performed by Sullivan et al (23) showed that, when asked about disclosure, 97% of more than 300 patients responded "I want to be told of serious, life-threatening diagnosis." More specifically, in another survey (25), 67% of more than 2,600 adults in the United States and Europe responded that they would make use of a test for early AD diagnosis once such a test became available. In accordance, a metaanalysis of 23 studies in more than 9,000 subjects revealed that, in the case of the cognitive impairment subgroup, 84% of the participants favored disclosure of the dementia diagnosis to them ( Fig.…”
Section: Disclosure Of Amyloid Imaging Resultsmentioning
confidence: 99%
“…However, in support of disclosure, a general questionnaire study performed by Sullivan et al (23) showed that, when asked about disclosure, 97% of more than 300 patients responded "I want to be told of serious, life-threatening diagnosis." More specifically, in another survey (25), 67% of more than 2,600 adults in the United States and Europe responded that they would make use of a test for early AD diagnosis once such a test became available. In accordance, a metaanalysis of 23 studies in more than 9,000 subjects revealed that, in the case of the cognitive impairment subgroup, 84% of the participants favored disclosure of the dementia diagnosis to them ( Fig.…”
Section: Disclosure Of Amyloid Imaging Resultsmentioning
confidence: 99%
“…80 These factors, combined with changes in diagnostic technologies forrisk-stratification, portendthat guidelines for the diagnosis and management of MCI will likely be in flux, and debated, over the next decade.…”
Section: Future Directionsmentioning
confidence: 99%
“…Among age-related conditions, perhaps none are more concerning or disheartening to both the individual and loved ones than the loss of memory and (in some cases) subsequent onset of dementia (Riley et al, 2014; Wikler et al, 2013). Dementia, of which Alzheimer's disease (AD) is the most common form, is a potentially debilitating condition which negatively impacts quality of life for both affected patients and caregivers and has tremendous associated healthcare costs (Boustani et al, 2007).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%